Dopamine D1 Receptor Agonist A-68930 Inhibits NLRP3 Inflammasome Activation, Controls Inflammation, and Alleviates Histopathology in a Rat Model of Spinal Cord Injury. Issue 6 (March 2016) - Jiang, Wu; Huang, Yan; He, Fan; Liu, Jia; Li, Maoqiang; Sun, Tiansheng; Ren, Wencheng; Hou, Jingming; Zhu, Liulong
Abstract : Study Design: A randomized experimental study. Objective: The aim of this study was to investigate the therapeutic efficacy and molecular mechanisms of dopamine D1 receptor agonist A-68930 in spinal cord injury (SCI) rats. Summary of Background Data: The inflammation induced by SCI includes maturation and secretion of pro-inflammatory cytokines interleukin (IL)-1β and IL-18 mediated by nucleotide-binding domain -like receptor protein 3 (NLRP3) inflammasome. Dopamine D1 receptor agonist A-68930 has been reported to exert neuroprotective effect via suppressing NLRP3 inflammasome activation in some central nervous injury models. However, whether A-68930 can exert nueroprotection in rat SCI models through inhibition of NLRP3 inflammasome activation has yet to be investigated. Methods: Eighty female Sprague–Dawley rats were randomly divided into 4 groups: sham group, SCI group, SCI + Vehicle (Veh) group, SCI + A-68930 group. The influences of A-68930 on the proinflammatory cytokines levels, histological changes, and locomotion scale were estimated. Results: SCI significantly promoted NLRP3 inflammasome activation and increased proinflammatory cytokines productions in SCI group as compared with sham group. A-68930 administration significantly inhibited NLRP3 inflammasome activation and reduced inflammatory cytokines levels. Moreover, A-68930 administration attenuated histopathology and promoted locomotion recovery. Conclusion: A-68930 can attenuate tissue damage and improve neurological function recovery, and the mechanism may be related to the inhibition of NLRP3 inflammasome activation. Level of Evidence: NA